Lateral root growth in Arabidopsis is controlled by short and long distance signaling through the LRR RLKs XIP1/CEPR1 and CEPR2. (3rd June 2018) - Dimitrov, I.; Tax, F. E.
ABSTRACT: Plants rely on lateral roots to explore their soil environment and to maximize their uptake of essential minerals and water. Here we present evidence that the receptor kinases XIP1/CEPR1 and CEPR2 regulate both the initiation of lateral root primordia and emergence of lateral roots locally in the root, while also controlling lateral root extension in response to shoot-derived sucrose in Arabidopsis plants. In addition, mutation of both of these receptors prevents seedlings from responding to sucrose in the media, resulting in longer lateral roots. These results, combined with previous data, establish XIP1/CEPR1 and CEPR2-dependent roles in short- and long-distance pathways regulating different stages of lateral root growth.